Assessment of dental anxiety and dental phobia among adults in Lebanon - Hiba Kassem El Hajj; Youssef Fares; Linda Abou-Abbas (BMC, 2021)
Abstract Background Dental anxiety continues to be a widespread problem affecting adult populations. The primary aim of our study was to evaluate the psychometric properties of the Lebanese Arabic version of the Modified Dental Anxiety Scale (MDAS-A) and to identify the optimal cut-off for assessing dental anxiety and dental phobia among adults in Lebanon. In addition, we sought to assess dental anxiety and phobia as well as their correlates among Lebanese adult patients. Methods A cross-sectional study was carried out on a sample of 451 dental adult patients aged between 18 and 65 years old. Information about demographic characteristics, previous bad dental experience, trauma's experience period, perception of a periodontal problem, sensation of nausea during dental treatment, the MDAS-A scale, and the Visual Analogue Scale for anxiety (VAS-A) were collected. Results MDAS-A exhibited evidence of adequate psychometric properties. The optimal cut-off was 12 for dental anxiety and 14 for dental phobia. Out of the total sample, 31.5% suffered from dental anxiety while 22.4% had a dental phobia. Multivariable analysis showed that the odds of dental anxiety and phobia were higher among females compared to males. Also, patients suffering from periodontal problem perceptions, bad dental experiences during childhood and adolescence, and the sensation of nausea during dental treatment were at a higher risk of developing dental anxiety and phobia compared to their counterparts. However, a higher level of education was found to be a protective factor against dental phobia among Lebanese adult patients. Conclusion The MDAS-A scale is a suitable tool for the routine assessment of dental anxiety and phobia among Lebanese adult patients. Identifying patients with dental anxiety at the earliest opportunity is of utmost importance for delivering successful dental care.